(untitled) (International relations and international law Journal, 2016)
The article scopes the problems relating the sphere of application of international criminal law. Last time a lot of researchers define the object of international criminal law including criminal offences of international character in a row with international crimes. Such points of views are found regarding to object and sources of international criminal law and persons engaged to international responsibility. After own analysis the author sums that criminal offences of international character like terrorism, human traffic, illegal trade of drugs can not be an object of research of international criminal law. Such conclusion based on the fact that responsibility for only international crimes in practice is realized by the International Criminal Court. The criminal offences of international character should not be an object of international criminal law because they lay under national courts` jurisdiction with application of national legal systems. The author notes such similarities of criminal offences of international character and international crimes like: common name as “conventional crimes”, realisation by organized criminal groups, necessarity for international co-operation for suppression. Differences between these types of crimes noted by the author are the different levels of social danger and applicability of national law and procedure. As a result, the author notes that for differentiation of competences of the ICC and national courts the ICC should prosecute only international crimes.